Is it Possible to Estimate Match Result in Volleyball: A new Prediction Model - Cengiz Akarçeşme (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
This study investigates the power of variables in a logistic regression model (the efficacy model or (EM)) to explain the match results in the Turkish Men’s Volleyball League (TMVL) and the Turkish Women’s Volleyball League (TWVL) in terms of the players’ positions. The dependent variable was the match result, and the power of the variables libero player efficiency (LPE), setter efficiency (SE), middle blocker efficiency (MBE), outside hitter efficiency (OHE) and universal player efficiency (UPE) were separately investigated for both genders. The EM accurately classified 83.45% of the games won and lost in the TWVL. The sensitivity (proportion of won games classified as won) and specificity (proportion of lost games classified as lost) was 85.03 and 81.88%, respectively. In the TMVL analysis, the classification accuracy, sensitivity and specificity were 78.23, 78.77 and 77.70%, respectively. Moreover, for both genders, the match results were chiefly explained by the SE, MBE, OHE and UPE. The LPE variable could not predict the results in the TWVL.